Two new species of philometrid nematodes (Nematoda: Philometridae) from the southern flounder Paralichthys lethostigma in the estuaries of South Carolina, USA - Moravec, Frantisek; de Buron, Isaure (Folia parasitologica, 2006)
Two new philometrid nematodes, Philometra overstreeti sp. n. and Philometroides paralichthydis sp. n., are described from female specimens collected from the southern flounder Paralichthys lethostigma Jordan et Gilbert (Paralichthyidae, Pleuronectiformes) in estuaries of South Carolina, USA. P. overstreeti is characterized by the presence of eight large, equal in size cephalic papillae, the absence of caudal projections, the body length of gravid females (14.10-27.06 mm) and the location in the host (among teeth). P. paralichthydis from the host's fins and the buccal cavity differs from its congeners mainly in possessing longitudinal cuticular ornamentations in addition to transverse ones or individual rounded bosses. It is the first species of Philometroides reported from flatfishes (Pleuronectiformes). A re-examination of type specimens of Margolisianum bulbosum Blaylock et Overstreet, 1999 showed that, in fact, nematodes belonging to two different species (now described to be new to science) and genera were confused in the original description of this taxon and in the diagnosis of Margolisianum. Since the male holotype of M. bulbosum cannot be identified to genus, Margolisianum bulbosum is a species inquirenda and a species incertae sedis. Consequently, Margolisianum becomes a genus inquirendus.
Keywords: hlístice; South Carolina; Jižní Karolína; Nematoda; Male; Animals; platýs; mužské pohlaví; ženské pohlaví; Female; Flounder; zvířata